Effects of embedded dipole layers on electrostatic properties of alkanethiolate self-assembled monolayers - Cabarcos, Orlando M.; Schuster, Swen (The journal of physical chemistry. C, Energy, materials, and catalysis, 2017)
Alkanethiolates (ATs) forming self-assembled monolayers (SAMs) on coinage metal and semiconductor substrates have been used successfully for decades for tailoring the properties of these surfaces. Here, we provide a detailed analysis of a highly promising class of AT-based systems, which are modified by one or more dipolar carboxylic acid ester groups embedded into the alkyl backbone. To obtain comprehensive insight, we study nine different embedded-dipole monolayers and five reference nonsubstituted SAMs. We systematically varied lengths of the alkyl segments, ester group orientations, and number of ester groups contained in the chain. To understand the structural and electronic properties of the SAMs, we employ a variety of complementary experimental techniques, namely, infrared reflection absorption spectroscopy (IRS), high-resolution X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), atomic force microscopy (AFM), and Kelvin probe (KP) AFM. These experiments are complemented with state-of-the-art electronic band-structure calculations. We find intriguing electronic properties such as large and variable SAM-induced work function modifications and dipole-induced shifts of the electrostatic potential within the layers. These observations are analyzed in detail by joining the results of the different experimental techniques with the atomistic insight provided by the quantum-mechanical simulations.
Gesehen am 05.04.2018